Financial market dynamics and regulation - Jesper Riedler (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
[Introduction] The current banking regulation laid down, for example, in the Capital Requirements Regulation and Directive (CRR/CRD IV) for the European Union, consist of a large number of detailed rules for diverse areas of bank risk such as market risk, liquidity risk, credit risk, and operational risk, just to mention the most important. Even for individual regulatory measures such as the minimum capital requirements, it is difficult to assess the effects on a single bank, but very hard to get an estimate for the complete banking sector. However, from an economic policy perspective it is necessary to know how a regulatory measure will affect economic development and growth. It would be of even higher importance to have such knowledge for the regulatory rulebook as a whole, but this seems to be far beyond the scope of theoretical or applied economic models. The aim of our project was to develop a multi-purpose agent-based model targeted to measure the effects of banking regulation, both for the banking sector and for the whole economy. A first important application is to find out if and how strongly banking regulation impacts monetary policy. In the years after the beginning of the financial market crises (i.e. in the years after 2008) the European Central Bank (ECB) did a good job in preventing a collapse of the banking sector in the Eurozone. Nevertheless, even after many years of very low costs of loans for private households and companies (both in nominal and real terms), growth rates of loans to the private sector and M3 are still below pre-crisis levels. Also inflation is still far below the target level of the ECB. This shows in a glance how difficult it is for the ECB to normalise the transmission mechanism of monetary policy. [...]
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: 330